Family Support and Colorectal Cancer Screening among Urban African Americans - Brittain, Kelly (2012)
Colorectal cancer (CRC) is the third leading cause of cancer death among African Americans. Less than 50% of African Americans have had CRC screening. This study examined the relationships between family support and influence, cultural identity, CRC beliefs, and a screening informed decision among 129 urban African Americans. Family support (p < .01) significantly predicted CRC beliefs and CRC beliefs significantly predicted informed decision (p < .01). Based on study results, practitioners should routinely assess family support and CRC beliefs with African Americans patients. This may improve patient-provider shared decision-making satisfaction and CRC screening adherence among African American patients.